The garuda purana and hindu death rituals:: exploring psychological dimensions through contemporary practices - Adhikary, Ramesh Prasad (Revista Perspectiva Científica, 2024)
Introduction: this research article explores The Garuda Purana, one of the 18 Maha Puranas of Hinduism, focusing on its prescriptions for death rituals and their psychological impact. The Garuda Purana offers detailed guidance on the conduct of funeral rites and the journey of the soul post-mortem. This study examines the psychological functions of these rituals, investigating how they assist individuals in navigating the grieving process, fostering emotional resilience, and maintaining mental equilibrium during bereavement. Objectives: The objective of this research is to explore how rituals prescribed in The Garuda Purana influence psychological well-being during the mourning process. Methods: mixed-methods approach was employed, comprising textual analysis of the Garuda Purana and thematic analysis of interviews with Hindu priests and bereaved family members. The textual analysis revealed Purana’s emphasis on rituals for purifying the soul, mitigating sins, and fostering communal support, providing a structured framework for navigating grief. Thematic analysis of interviews underscored the psychological benefits of ritual participation, highlighting themes of solace, control, and communal support among participants. Results: findings indicate that engaging in these rituals offers a sense of purpose and empowerment to the bereaved, aiding in the acceptance of loss and mitigating existential anxieties. The communal nature of these rituals was found to play a crucial role in providing emotional support and solidarity within the grieving community.